Damage detection in a precast structure subjected to an earthquake: A numerical approach. (15th November 2016) - Pierdicca, A.; Clementi, F.; Maracci, D.; Isidori, D.; Lenci, S.
Highlights: A new approach for a real-time SHM system is proposed to outline a possible post-seismic scenario. The damage indices are calculated throught performing nonlinear static and dynamic analyses. The procedure allows the localization and quantification of the damage. The procedure may help practitioners in evaluating of post-seismic structural conditions. Abstract: Seismic risk mitigation is a relevant issue in European regions, such as Italy, characterized by the presence of a large stock of vulnerable existing industrial buildings. Through a case study, the article proposes an integrated novel approach for the diagnosis of structures after a seismic event. The suggested monitoring system is based on recording the accelerations of a real structure during an earthquake and on their introduction as input into a Numerical Model (NM), suitably tuned, to outline a possible post-earthquake scenario. The leading idea of this approach is to provide an estimation of the health and remaining life of monitored structures and to detect and quantify the damage, some of the crucial issues of Structural Health Monitoring (SHM). The technique is applied to a real structure, an industrial building liable to some seismic vulnerabilities. The structure has never been subjected to an earthquake, so the actual accelerations could not be recorded. For this reason, they are acquired from a second NM subjected to real and simulated earthquakes.